An Introduction to the (Meta-) Theory of Structures - Duskin, John (My University, 1963)
This thesis is intended as a self-contained, expository introduction to material found in Chapter IV of Bourbaki’s Theorie des Ensembles. With a minimum of external reference, it presents all relevant logical and set-theoretic background material and then develops and extends the notions of "species of structure", "intrinsic terms", "canonical mappings", "processes of deduction", "morphism", etc. found in this work.
Keywords: metatheory; theory of structures